The Oxford handbook of banking - Berger, Allen N.; Molyneux, Philip; Wilson, John O. S. (Oxford : Oxford University Press, 2012)
This handbook provides an overview and analysis of state-of-the-art research in banking written by leading researchers in the field. It strikes a balance between abstract theory, empirical analysis, and practitioner and policy-related material.
Originally published: 2010.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Banks and banking